The Role of Digital Technology in Enhancing Access to Information and Public Services for Marginalized Communities - Hartana; Didik Suhariyanto; Dedy Irwan; Redemptus Dr Ferento Nino De Ferento Nino (Pengabdian: Jurnal Abdimas, 2025)
Background. Mainstream digital public infrastructure (DPI) often fails to serve marginalized communities, reinforcing the “digital divide” caused by exclusionary design that overlooks barriers such as low literacy and lack of digital trust. Purpose. To quantitatively analyze the causal impact of a co-designed, voice-first mobile application on access to information and public services for marginalized communities. Method. The study employed a mixed-methods, quasi-experimental Difference-in-Differences (DiD) design, comparing an intervention group (N = 120) with a control group (N = 115). The intervention’s impact was measured using the validated Digital Access and Agency Index (DAAI). Results. The intervention group showed a transformative and statistically significant improvement: their service application rate increased from 8.3% to 62.5%, and their mean DAAI score rose by 22.38 points (p < 0.001), while the control group showed no change. Conclusion. The digital divide is fundamentally a design problem rather than a user deficit. The co-design process, by fostering social trust, served as the main causal mechanism for reducing digital exclusion, demonstrating that inclusive, human-centered design can effectively empower vulnerable populations.